BERAT BADAN LAHIR RENDAH SEBAGAI FAKTOR RISIKO DOMINAN TERHADAP KEJADIAN GAGAL TUMBUH PADA ANAK USIA 6-24 BULAN - Siti Syofiatul Rohmah; Suyatno Suyatno; Martha Irene Kartasurya (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Growth faltering on child age 6-24 months is the beginning of protein energy malnutrition. Tanjung Mas is a coastal area in Semarang which had the 2nd highest number of undernourished children. The purpose of this research was to analyze the related factors of growth faltering on childrens age 6-24 months in Tambak Lorok Semarang. This observational study was conducted in a cross sectional design. Eighty five subjects were selected through clustered random sampling. Data were collected through interviews with structured questionnaires and food intake obtained from 2x24 hour recall. Data analysis was done in chi square test and multiple logistic regression. The results showed that 18.8% children were in growth faltering. Children with deficit energy intake 30.6% and deficit protein 25.9%. Children with deficit zinc intake 29.4%, deficit iron 36.5%, deficit vitamin A 23.5%, deficit vitamin C 42.4%, and deficit vitamin D 62.4%. Almost half of the respondents (48.2%) had low food diversity. Incidence of diarrhea in the last 2 months was 21.2% and, upper respiratory tract infection was 85.9%. Total 21.2% with low birthweight history. Energy (p=0,030), protein (p=0.006), zinc (p=0.021), vitamin C intake (p=0,0001), and low birthweight history (p=0,0001) were related to growth faltering on children aged 6-24 months. The most associated factors to growth faltering was low birthweight (p=0,001). Children with low birthweight increased the risk of growth faltering by 10,2 times. Factors related to growth faltering were macro and micro nutrient intake and low birth weight.